2002
DOI: 10.1074/jbc.m201582200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Insulin Gene Promoter through a Direct Effect of Hepatocyte Nuclear Factor 4α

Abstract: Maturity onset diabetes of the young, subtype 1 (MODY1), is associated with defective glucose-dependent insulin secretion from pancreatic beta cells. MODY1 is caused by mutation in the transcription factor hepatocyte nuclear factor 4␣ (HNF4␣). To understand better the MODY1 phenotype, we tested whether HNF4␣ was able to modulate directly the insulin gene promoter. Transfection of cultured 293T cells with an HNF4␣ expression vector led to 10-fold activation of a cotransfected reporter plasmid containing the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 47 publications
(47 reference statements)
1
56
1
Order By: Relevance
“…Failure to activate transcription by missense MODY-1 mutants is ascribed to impaired dimerization, DNA binding, recruitment of coactivators, or protein destabilization (11)(12)(13)(14). MODY-1 is characterized by early onset, autosomal dominant inheritance of impaired pancreatic insulin secretion (4,18), in line with the direct (HNF-4␣/DR-1-mediated (19)) and indirect (HNF-1␣-mediated (7)) modes of transcriptional activation of the insulin gene promoter by HNF-4␣. Concomitantly, MODY-1 patients are hypolipidemic (6), in line with the profile of liver HNF-4␣-responsive genes coding for apolipoproteins (e.g.…”
Section: Hnf-4␣mentioning
confidence: 99%
“…Failure to activate transcription by missense MODY-1 mutants is ascribed to impaired dimerization, DNA binding, recruitment of coactivators, or protein destabilization (11)(12)(13)(14). MODY-1 is characterized by early onset, autosomal dominant inheritance of impaired pancreatic insulin secretion (4,18), in line with the direct (HNF-4␣/DR-1-mediated (19)) and indirect (HNF-1␣-mediated (7)) modes of transcriptional activation of the insulin gene promoter by HNF-4␣. Concomitantly, MODY-1 patients are hypolipidemic (6), in line with the profile of liver HNF-4␣-responsive genes coding for apolipoproteins (e.g.…”
Section: Hnf-4␣mentioning
confidence: 99%
“…The occupancy by HNF4α of a substantial fraction of expressed genes suggests that HNF4α is a widely acting transcription factor and crucial for development and proper secretary function of pancreatic β cells. Furthermore, BartoovShifman et al [10] found that HNF4α could activate insulin gene directly, through a previously unrecognized cis element. Clinical researches have indicated that mutations in gene encoding HNF4α result in maturityonset diabetes of the young type 1, characterized by autosomal dominant inheritance, early onset and impairment of glucose-stimulated insulin secretion (GSIS) [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Pdx-1 induces glucokinase, Glut2, and insulin gene expression in the mature pancreas (28,29). HNF4α regulates insulin release through controlling mitochondrial metabolism of glucose and HNF1α, Glut2, and insulin gene expression (30,31).…”
mentioning
confidence: 99%